2017
DOI: 10.1002/app.45263
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of thermal and tribological behaviors of PTFE‐based silicon composites filled with AlN and flake graphite particles

Abstract: The thermal and tribological properties of silicon composites were improved by choosing polytetrafluoroethylene (PTFE) as a thickener and alumina nitride (AlN) and flake graphite (FG) as thermal conductive additives, producing AlN‐modified, FG‐modified, and AlN/FG‐modified PTFE‐based thermal silicon composites (AlN–PTSC, FG–PTSC, and AlN/FG–PTSC, respectively). Three‐dimensional network‐configuration representative volume element models were built to investigate the thermal properties of these composites by ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The finite element method has been rapidly enhanced with the development of electronic computers, widely used to solve the problems in mechanics, heat transfer, and materials design. 21,22 Xi et al 23 used ANSYS software to simulate the effect of AlN and graphite particles on the thermal conductivity and friction properties of the PTFE composites. Huang et al 24 used ANSYS software to study the effect of ZnO and MoS 2 solid lubricants on the high-temperature tribological properties of M50 steel matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…The finite element method has been rapidly enhanced with the development of electronic computers, widely used to solve the problems in mechanics, heat transfer, and materials design. 21,22 Xi et al 23 used ANSYS software to simulate the effect of AlN and graphite particles on the thermal conductivity and friction properties of the PTFE composites. Huang et al 24 used ANSYS software to study the effect of ZnO and MoS 2 solid lubricants on the high-temperature tribological properties of M50 steel matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, abrasive wear dominates at low temperatures and adhesive wear prevails at high temperatures for self‐lubricating polymer composites 21 . The accumulation of frictional heat at the sliding interface normally results in the softening or even melting of polymer substrate, thereby leading to the peeling off or shear deformation of polymer matrix 57–59 . Therefore, in situ monitoring the temperature increase of sample blocks during sliding tests provides an indirect evidence to determine the wear mechanism and frictional properties of polymer composites, which is also critical for their applications in industrial sectors.…”
Section: Resultsmentioning
confidence: 99%
“…The finite element method has been rapidly enhanced with the developed electronic computers, widely used to solve the problems in mechanics, heat transfer, and materials design 25 . Recently, Xiang et al 26 applied ANSYS software to establish a three‐dimensional volume element model of the composites, and the numerical calculation results were in good agreement with the experimental results. Quazi et al 27 made to investigate the effect of friction on the fatigue life of PTFE through experimental and ANSYS numerical analysis and found that due to the small friction coefficient of PTFE, shape optimization should be considered to avoid the design of sharp notches when used as a base material.…”
Section: Introductionmentioning
confidence: 92%